Communication Evaluation Using Safe Communication Methods in Coordination, Forwarding Patient Information by Phone between hospital - สงวนพันธ์ุ ปรานอม (Journal of Health Sciences and Wellness, 2019)
Abstract Receiving a referral on the phone is a coordination that has 2 people involved. It is a speech transfer using electronic system tools as a communication tool. Which may cause the transmission of necessary patient information is lost or not complete, resulting in delayed healing. Affecting the life of patients using SBAR as a communication tool which has elements from the four elements: 1) S (situation) is a report of patient information with the situation of problems 2) B (background) is background information about the history of illness and treatment. 3) A (assessment) is the data obtained from the evaluation of patients for use in assisting and caring. 4) R (recommendation) is a recommendation for further solutions in each duty. The Referral Center of Siriraj Hospital has developed such tools to be a form that has 4 elements. With the result that the personnel involved in the operation are 100% satisfied with Situation, Background, Recommendation, but the same assessment is 75%. And also has a good result that 100% of the personnel expressed their opinion is to understand health information, confidence in receiving patient health information, easy form, easy to record 100%